T-Cell Proapoptotic and Antifibrotic Activity Against Autologous Skin Fibroblasts in vitro Is Associated With IL-17A Axis Upregulation in Systemic Sclerosis - Vettori, Serena; Barra, Giusi; Russo, Barbara; Borgia, Alessia; Pasquale, Giuseppe; Pellecchia, Luciana; Vicedomini, Lucia; De Palma, Raffaele (Frontiers in Immunology, 2020)
Background. Systemic sclerosis (SSc) T cells can induce apoptosis of autologous skin fibroblasts in vitro. Th17 cells have been reported to increase in SSc patients, and interleukin-17A (IL-17A) has a profibrotic function. We used a system based on T-cell-autologous fibroblast co-cultures to further investigate a possible role of IL-17 in SSc. Methods. T cells from diffuse SSc patients were co-cultured with autologous skin fibroblasts. IL17A mRNA was assessed by real-time PCR in co-cultured and control T cells, while IL17RA, CXCL1, CCL2, CCL3, COL1A1, COL3A1, CTGF, TGFBR2, SMAD3 mRNAs were assessed in co-cultured and control fibroblasts. In subset experiments, co-cultures and control cells were treated with either IL-17A or IL-17A plus anti-IL17 receptor monoclonal antibody (α-IL-17RA mAb). Chemokine and procollagen type I (PCI) production was further investigated at the protein level in cell culture supernatants by multiple suspension immunoassay and sandwich ELISA, respectively. Co-cultured and control fibroblasts were also stained with Annexin V and analyzed by flow-cytometry. Results. T cell-fibroblast co-cultures overexpressed IL17A and IL17RA. Furthermore, co-cultured fibroblasts upregulated IL-17A targets CXCL1, CCL2, and CCL3, while COL1A1, COL3A1, CTGF, and two key effectors of the TGF-β signaling, TGFBR2 and SMAD3 were found downregulated. Consistently, chemokine concentrations were increased in co-culture supernatants, while PCI levels were reduced, especially after stimulation with ectopic IL-17A. Finally, simultaneous anti-IL-17RA mAb treatment restored PCI levels and reduced fibroblast apoptosis in IL-17A-stimulated co-cultures. Conclusion. These data suggest that IL-17A upregulation might play a role in modulating T cell-mediated antifibrotic and proapoptotic effects in co-cultured autologous skin fibroblasts.